PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PERTANIAN PROVINSI SULAWESI BARAT - Adnan, Jumaati; Ruliaty, Ruliaty (COMPETITIVENESS, 2018)
Abstract This study aims to find out and analyze the effect of compensation and work discipline on employee performance in the Office of agriculture of Sulawesi Province.The design used in this study is adescriptive method of survey with regression techniques. The population in this study was all employees in the Agriculture Office of West Sulawesi Province which amounted to 46 employees. Sampling techniques used in this study is saturated sampling techniques or census, namely the determination of the number of samples from all members of the population of 46 people. The data collection techniques used in this study are documentation and questionnaires. Documentation is used to collect information about the overview (profile, vision, mission,). Questionnaires are used to obtain data on Employee Performance, compensation, and Work Discipline. The results showed that. Compensation has a significant positive influence on the performance of employees of the Agriculture Office of West Sulawesi Province with P= 0.009<0.05 with a cofisien value of 0.272. This indicates that the better the compensation owned by employees, the better the performance, while the Motivation variable has an insignificant influence on employee performance. With P=0.139>0.05 with a coeffiien value of 0.127. this indicates that employee work motivation does not affect employee performance. And the next variable discipline has a significant positive influence on employee performance with P=0.001<0.05 with a coeffiien value of 0.403. This shows that the discipline of work at the Agriculture Office of West Sulawesi Province is getting bailk. It can be concluded that compensation and discipline of work is very influential oada pegwai performance, because the success of an organization and achieving the objectives of oraganizationKeywords: Compensation, Motivation, Discipline and Performance.